Pelatihan Dan Pemberdayaan Kader Dan Pendamping Keluarga Tentang Faktor Risiko Penyakit Tidak Menular (PTM) Di Posbindu Berkah Barokah Desa Limamar Wilayah Kerja Puskesmas Astambul - sajidah, ainun; Mariana , Evi Risa; Hammad, Hammad; Rahmah, Adila Alfina; Nazmi, Syaima; Kaila, Wafa (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
Based on the NCD data in the working area of Puskesmas Astambul, there is a tendency of increase from 2017 to 2020. In 2017, there were 1,780 cases of hypertension and 109 cases of diabetes mellitus (DM). Although the cases of hypertension and diabetes mellitus decreased in 2021, they remained high with 757 and 241 cases respectively. However, cases of hypertension increased again in 2022 to 1,480 cases. From this data, it can be seen that the most common NCDs in the working area of Puskesmas Astambul are hypertension and diabetes mellitus. The goal of the community service is to enhance knowledge and provide services to target partners regarding the prevention and control of non-communicable diseases (Hypertension and Diabetes Mellitus) through